Macroalgal-derived protein hydrolysates and bioactive peptides: Enzymatic release and potential health enhancing properties. (November 2019) - Pimentel, Filipa B.; Alves, Rita C.; Harnedy, Pádraigín A.; FitzGerald, Richard J.; Oliveira, M. Beatriz P.P.
Abstract: Background: Macroalgae are a natural source of valuable compounds for different applications. Despite the high protein content (up to 47%) and complete essential amino acid profile in some species, their protein fraction is still relatively underexplored. Besides the potential as alternative protein sources, macroalgae can also provide bioactive peptides and other proteinaceous compounds with biological value. Scope and approach: In this review, data associated with macroalgal nitrogenous components, particularly peptides and protein hydrolysates, are presented and discussed, especially regarding their potential health properties and methodologies employed to obtain and isolate them. Key findings and conclusions: Obtaining these compounds and assessing their biological activities involves a combination of preparation and analytical steps ( e.g. isolation, purification, detection and quantification). Hydrolysis of macroalgal proteins using different proteinases generates multiple peptides with a broad range of biological activities. Further research and innovation will allow the development of more efficient production processes and will improve the range of applications. Current scientific evidences regarding the potential health benefits of macroalgae-derived proteinaceous compounds highlight the need of additional investments to effectively transfer promising findings into market driven opportunities. Graphical abstract: Image 1 Highlights: Macroalgae contain proteinaceous compounds with numerous biological functions. Enzymatic protein hydrolysis generates new peptides with different biological actions. Methodologies to obtain and isolate macroalgae-derived peptides are presented. Studies are needed to transfer scientific knowledge into commercial opportunities.